Features of Designing Computer Control Systems for Precision Thermoelectric Coolers - Dzundza, B.S.; Kostyuk, O.B.; Dashevsky, Z.M. (Physics and Chemistry of Solid State, 2021)
An effective electrical circuit and an operating algorithm have been developed, and a working sample of a thermoelectric precision thermostat has been designed with the possibility of autonomous operation, continuous monitoring and recording of the temperature log using a computer or smartphone. It is shown that the developed algorithm provides effective shockless control and an accuracy of maintaining the temperature of 0.03°C, with a power consumption of 3-7 W. A design and a specialized computer control system for a multistage cryogenic thermoelectric cooler have been developed.